2020
DOI: 10.1088/1742-6596/1434/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nitrogen fertilizer on the aquatic environment in the Upper Tondano watershed, North Sulawesi Province

Abstract: Nitrogen fertilization is needed as a source of nitrogen in the growing plants. Nitrogen in the environment will undergo a transformation in the form of compounds such as nitrate (NO3 −) and nitrite (NO2 −). The transformation from nitrogen to nitrate, nitrite, will have a negative impact on the aquatic environment namely the formation of toxic conditions. The main purpose of this research was to study the residual nitrogen fertilizer in the outlet of paddy irrigation upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The transportation of nutrient residues resulting from fertilisation practices, including the application of urea fertiliser, will be facilitated through irrigation systems. Urea (CO (NH2)2) undergoes hydrolysis to yield ammonium nitrate, which is then absorbed by plants in the form Poor of ammonium (NH4 + ) and nitrate (NO3 -) [19][20][21]. In the event that these nutrients are not taken up by plants, they may be carried into irrigation canals and water bodies, such as rivers.…”
Section: Figure 5 Grey Water Footprint Score Performance On Paddy And...mentioning
confidence: 99%
“…The transportation of nutrient residues resulting from fertilisation practices, including the application of urea fertiliser, will be facilitated through irrigation systems. Urea (CO (NH2)2) undergoes hydrolysis to yield ammonium nitrate, which is then absorbed by plants in the form Poor of ammonium (NH4 + ) and nitrate (NO3 -) [19][20][21]. In the event that these nutrients are not taken up by plants, they may be carried into irrigation canals and water bodies, such as rivers.…”
Section: Figure 5 Grey Water Footprint Score Performance On Paddy And...mentioning
confidence: 99%
“…After the concentration of harmful substances, such as ammonia nitrogen, in the aquatic environment of the aquaculture reaches a certain value (Wantasen et al, 2020), non-ionized ammonia is prone to entering the bodies of the aquatic environment through the cell membrane, leading to physiological imbalance and disorder, leading to tissue hypoxia and toxicity (Li et al, 2007). At the same time, a certain concentration of nitrite can inhibit and affect the growth, development, and reproduction of aquaculture organisms, which can damage or even kill the oxygen-carrying capacity of hemocyanins (Chand & Sahoo, 2006).…”
Section: Changes In Water Quality Of Aquaculture Barrels In a Circula...mentioning
confidence: 99%
“…A strict policy in the local administration for converting productive land to annual crops and rice paddies is to control sedimentation in Lake Tondano (Walangitan et al 2012). Another research in Lake Tondano found that nitrogen (from agricultural activity surrounding the lake) transformed into nitrate, nitrite, and ammonia, which made Eichhornia crassipes became an invasive species (Wantasen et al 2012). Therefore, the local farmers need proper formal education and farming skill (Lubis & Langston 2015;Purba & Pratiwi 2020).…”
Section: Introductionmentioning
confidence: 99%